Antimicrobial action of essential oil of Lippia origanoides H.B.K. - Antonio Linkoln Alves Borges Leal; Antonio Lima Braga; Brenda de Araújo Barbosa; Aldenora Maria Ximenes Rodrigues; Francisco Anderson Fortuna de Carvalho Teixeira; Kelly Maria Rêgo da Silva; Enéas Costa Júnio; Thalys Ribeiro de Sousa Leite; Mateus Sávio Amorim; Antônia Maria das Graças Lopes Citó; Maria das Graças Freire de Medeiros Carvalho (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2019)
The Lippia oils are well known for the treatment of respiratory problems, as well as their oils have compounds that are possibly good antimicrobial agents. In order to confirm the seasonal differences and also to observe the potential to influence the antimicrobial activity, it was evaluated antimicrobial activity of the essential oil of Lippia origanoides H K B against the strains of Staphylococcus aureus, Escherichia coli and Candida albicans. Methodology: leaves of Lippia origanoides H.B.K. were harvested in the municipality of José de Freitas - PI, followed by their plants by the hydrodistillation process. Afterwards the oil was subjected to the analysis of techniques by Gas Chromatography coupled to GC-MS Mass Spectrometry for the identification of its most important components. The test for its activities was bactericidal and fungicidal at the concentrations of 100, 300, 600 and 900 μg / mL. According to the analysis of the oil in the study, the results are classified as chemotactic C, since it presents 55.53% of thymbrite as the majority of the total area analyzed. In addition, it presents 18.87% of carvacrol and 18.03% of p - cimene, the latter being a precursor of thymol and carvacrol. Events reported to results are due to the major compounds present in the oil. After 24 hours of growth, inhibition can be detected in some of the tested, as well as, it was noticed that the diluted in saline did not present positive results as expected for control. However, the oil at concentrations of 100, 300, 600 and 900 μg / ml inhibited growth against E. coli. Inhibition of the Staphylococcus aureus strain was observed at concentrations of 300, 600 and 900 μg / mL and against candida albicans there was inhibition at the concentrations of 300, 600 and 900 μg / mL. At the concentration of 100 μg / mL against the last strains there was no inhibition. The antimicrobial action is derived from the essential oil itself and the main responsible for it are the main components present, thymol and carvacrol and or association thereof, as well as resulting from hydrophobicity, permeability of the membrane. Conclusion: It was perceived that the essential oil of Lippia origanoides H. B. K. presented antimicrobial action as strains of Staphylococcus aureus, Escherichia coli and Candida albicans. At the concentration of 600 μg / mL there was a greater action against bacterial strains and against the fungal strain, 900 μg / mL, with a higher inhibition index. Therefore, a L. origanoides presents itself as promising for the development of new phytotherapics, faster and at a lower cost.